1991
DOI: 10.1029/91jd00609
|View full text |Cite
|
Sign up to set email alerts
|

Ground‐based infrared measurements of HNO3 total column abundances: Long‐term trend and variability

Abstract: The long-term trend and variability of the total column amount of atmospheric nitric acid (HNO3) have been investigated based on time series of infrared solar absorption spectra recorded at two remote high-altitude sites, the International Scientific Station of the Jungfraujoch (ISSJ) in the Swiss Alps (altitude 3.6 km, latitude 46.5øN, longitude 8.0øE) and the National Solar Observatory McMath solar telescope facility on Kitt Peak (altitude 2.1 km, latitude 31.9øN, longitude 111.6øW), southwest of Tucson, Ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 51 publications
(16 reference statements)
2
17
0
Order By: Relevance
“…Values of potential vorticity (PV) at the potential temperature of 520 K (∼50 hPa) gathered from the Met Office fields 1 for MLS analyses have further been used to represent the size, the shape and the strength of the polar vortex and are superim-1 available at: https://mls.jpl.nasa.gov/dmp/ chosen mid-latitude (Moshiri,44 • N, 142.3 • E) and polar sites (Ny Alesund,78.9 • N 11.9 • E) in the Northern Hemisphere vary on average between 2.50×10 16 molecules cm −2 in January to 1.35×10 16 molecules cm −2 in July and between 3.15×10 16 molecules cm −2 in January to 1.89×10 16 molecules cm −2 in July, respectively. These large-scale spatial and seasonal variations in the HNO 3 total columns are fully consistent with the photochemical processes occurring in the stratosphere (Austin et al, 1986;Rinsland et al, 1991;Santee at al., 1999 andreferences therein, Santee et al, 2004;Urban et al, 2008, among others).…”
Section: Global Distributionssupporting
confidence: 57%
“…Values of potential vorticity (PV) at the potential temperature of 520 K (∼50 hPa) gathered from the Met Office fields 1 for MLS analyses have further been used to represent the size, the shape and the strength of the polar vortex and are superim-1 available at: https://mls.jpl.nasa.gov/dmp/ chosen mid-latitude (Moshiri,44 • N, 142.3 • E) and polar sites (Ny Alesund,78.9 • N 11.9 • E) in the Northern Hemisphere vary on average between 2.50×10 16 molecules cm −2 in January to 1.35×10 16 molecules cm −2 in July and between 3.15×10 16 molecules cm −2 in January to 1.89×10 16 molecules cm −2 in July, respectively. These large-scale spatial and seasonal variations in the HNO 3 total columns are fully consistent with the photochemical processes occurring in the stratosphere (Austin et al, 1986;Rinsland et al, 1991;Santee at al., 1999 andreferences therein, Santee et al, 2004;Urban et al, 2008, among others).…”
Section: Global Distributionssupporting
confidence: 57%
“…The site has been shown to be excellent for studies on new particle formation (Bianchi et al 2016) or aerosol-cloud interaction, including mixed-phase and glaciated clouds Verheggen et al 2007). In addition, remote sensing investigations have been performed by FTIR spectroscopy, which allows for quasisimultaneous investigation of total column concentrations of a large number of gaseous constituents (e.g., Barret et al 2002Barret et al , 2003aDe Mazière et al 1999;Dils et al 2011;Duchatelet et al 2009Duchatelet et al , 2010Krieg et al 2005;Mahieu et al 1997;Melen et al 1998;Rinsland et al 1991Rinsland et al , 1992Rinsland et al , 1996Rinsland et al , 2000Rinsland et al , 2008Vigouroux et al 2007;Zander et al 2008Zander et al , 2010. JFJ is exposed mostly to FT air masses in autumn and winter.…”
Section: Region Vi: Europementioning
confidence: 99%
“…Long-term changes in HNO 3 have been studied by use of ground-based observations of total columns, and spacebased, vertically resolved HNO 3 profiles. In an analysis of data comprised of solar spectra recorded with a grating spectrometer in June 1951 and a set of observations obtained with a Fourier transform spectrometer between June 1986 and June 1990, all from the International Scientific Station of the Jungfraujoch in Swiss Alps, Rinsland et al (1991) found no significant change in the June HNO 3 total column over this time span. Randel et al (1999) (Rinsland et al, 2003).…”
Section: Introductionmentioning
confidence: 99%